Evolutionary analysis of landscape ecological risk in Baili Rhododendron National Forest Park. - Yin Yu; Wengang Cui; Suihua Liu; Ting Yu; Yang Song (PLoS ONE)
It is significant to research the ecological risk of land use landscape to promote ecological conservation and restoration. The characteristics of land use dynamic change in Baili Rhododendron National Forest Park were analyzed based on GlobeLand30 data for three periods in 2000, 2010 and 2020. With the support of the landscape ecological risk evaluation model and spatial analysis methods, the features of spatial and temporal differentiation of ecological risk and its spatial correlation in the study area were evaluated. The results show that (1) the landscape pattern changed visibly from 2000 to 2020, the comprehensive land-use dynamics increased from 8.53% to 9.66%, and the land use dynamics are greatest and change most dramatically on construction sites; (2) the landscape ecological risk level of the study area as a whole showed a declining trend, and 96.82% of the ecological risk plot index decreased, and the risk distribution was dominated by lower risk, medium risk and higher risk areas; (3) landscape ecological risk was spatially positively correlated across all time periods, and the spatial aggregation was gradually weakened, with the distribution of LH and HL areas dispersed and the distribution of HH and LL areas concentrated. The overall landscape ecological risk index has witnessed a decline, indicating a positive trajectory in the development of the ecological environment.